Possible applications for combined lenvatinib and pembrolizumab in advanced endometrial carcinoma - K. V. Menshikov; A. V. Sultanbaev; Sh. I. Musin; I. A. Menshikova; N. I. Sultanbaeva; A. A. Izmailov; A. A. Fatikhova; D. O. Lipatov; G. A. Serebrennikov (Креативная хирургия и онкология, 2023)
Endometrial cancer is one of the most common gynaecological cancers in both the United States and the Russian Federation, and the rate continues to rise. Although early-stage endometrial cancer is associated with a favourable 5-year survival rate (96%), this rate in patients with distant metastases accounts for only 18%. A combination of paclitaxel and carboplatin is standard first-line therapy for advanced, recurrent and metastatic endometrial carcinoma. Pembrolizumab, a monoclonal antibody targeting the programmed death-1 receptor, is approved for therapy of metastatic solid tumors with high microsatellite instability that have progressed aft er previous therapy and have no alternative treatment options. Lenvatinib is an oral multikinase inhibitor that blocks vascular endothelial growth factor receptors 1-3, fibroblast growth factor receptors 1-4, platelet-derived growth factor receptor alpha, RET and KIT. Phase II and III studies (KEYNOTE-146/ Study111 and KEYNOTE-775) on the combination of lenvatinib and pembrolizumab in advanced endometrial carcinoma, irrespective of MMR and MSI status, have shown new potential for the treatment of this pathology. Th e results obtained, including progression-free and overall survival, allow the combination of lenvatinib and pembrolizumab to be considered a new standard for the treatment of this pathology.